THE 5S METHOD AND ITS INFLUENCE ON EMPLOYEE WORK REQUIREMENT PRACTICES WHICH CAN HAMPER LEAN SERVICE INTRODUCTION - Ulrych, Wojciech (Journal of Positive Management, 2020)
Purpose: Implementing new methodology requires a new way of thinking and behaviour. The introduction of lean can bring about problems that can derive from adapting to such a change, and also from employees being used to established customs, and from a lack of knowledge regarding the change. As a consequence, employee work requirement (EWR) practices may appear which can hamper lean introduction. This paper is an attempt to show how the aforementioned EWR practices can be reduced by the most basic lean method called the 5S`s. Methodology: Based on the author's own research a model has been developed. Modeling of structural equations required an indication of the theoretical model. A 5 point Likert scale questionnaire was developed and used. Findings: The 5S method can indeed decrease EWR practices and its usage is of the highest importance during the initial five years of lean service introduction. Implications/ limitations for practice: The EWR practices support each other which means that managers can spot them all in practice. This is why the most important thing is the appropriate introduction of the 5S method which constitutes the future success of lean service methodology. The research sample consisted of 173 purposefully selected lean-oriented service departments. Originality/value: The 5S - EWR model shows how well the fundamental 5S tool can manage with initial problems which derive from both a business model change and lean requirements. Keywords: employee work requirement practices, lean service, problems in lean introduction, the 5S method Paper type: Research paper